A Trace of Hope (a Keri Locke Mystery--Book #5) - Blake, Pierce (Lukeman Literary, 2018)
"A dynamic story line that grips from the first chapter and doesn't let go." --Midwest Book Review, Diane Donovan (regarding Once Gone) From #1 bestselling mystery author Blake Pierce comes a new masterpiece of psychological suspense. A TRACE OF HOPE is the final book in the Keri Locke series, bringing the series to a dramatic conclusion. In A TRACE OF HOPE (Book #5 in the Keri Locke mystery series), Keri Locke, Missing Persons Detective in the Homicide division of the LAPD, is closer than she's ever been to finding her daughter. Finally, she gets a fresh lead-and this time, she will do whatever it takes to bring her home alive. At the same time, a new, urgent case is assigned to Keri: an 18 year old girl has gone missing after being hazed by her sorority. As the race is on to find her, Keri plunges deep into the world of pristine college campuses, and comes to realize that all is not what it seems. A dark psychological thriller with heart-pounding suspense, A TRACE OF HOPE is book #5 in a riveting new series-and a beloved new character-that will leave you turning pages late into the night. "A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone)
Keywords: Krimi, detektivky